Developing a new health‐related policy analysis tool: An action research cooperative inquiry approach. (27th June 2019) - Casey, Mary; Rohde, Daniela; Brady, Anne‐Marie; Fealy, Gerard; Hegarty, Josephine; Kennedy, Catriona; McNamara, Martin; Nicholson, Emma; O'Connell, Rhona; O'Connor, Laserina; O'Leary, Denise; O'Reilly, Pauline; et al.
Abstract: Aim: To develop a tool for the analysis of nursing, midwifery and health‐related policy and professional guidance documents. Background: Analysis tools can aid both policy evaluation and policy development. However, no framework for analysing the content of professional regulation and guidance documents among health care professionals currently exists. Method: This study used an action research, cooperative inquiry design. Data were generated from two integrative literature reviews and discussions held during the cooperative inquiry meetings. Results: A set of key themes to be considered in the development or evaluation of health policy or professional regulation and guidance documents were identified. These themes formed the basis of the six domains considered by the Health‐related Policy Analysis Tool (HrPAT): Context, Process, Content, Stakeholder Consultation, Implementation and Evaluation. Conclusion: Use of the HrPAT can assist in policy development, evaluation and implementation, as well as providing some retrospective analytical insights into existing health policies. Implication for Nursing Management: Professional regulation documents, guidelines and policy reports should be capable of being scrutinized for their content, quality and developmental process. The HrPAT can assist relevant stakeholders in the development, analysis and evaluation of such documents, including local, service‐level policies and guidelines.